The IMGT/HLA database - Robinson, James (Oxford University Press, 2013)
It is 14 years since the IMGT/HLA database was first released, providing the HLA community with a searchable repository of highly curated HLA sequences. The HLA complex is located within the 6p21.3 region of human chromosome 6 and contains more than 220 genes of diverse function. Of these, 21 genes encode proteins of the immune system that are highly polymorphic. The naming of these HLA genes and alleles and their quality control is the responsibility of the World Health Organization Nomenclature Committee for Factors of the HLA System. Through the work of the HLA Informatics Group and in collaboration with the European Bioinformatics Institute, we are able to provide public access to these data through the website http://www.ebi.ac.uk/imgt/hla/. Regular updates to the website ensure that new and confirmatory sequences are dispersed to the HLA community and the wider research and clinical communities. This article describes the latest updates and additional tools added to the IMGT/HLA project.